Magnetotelluric signatures of the complex tertiary fold–thrust belt and extensional fault architecture beneath Brøggerhalvøya, Svalbard - Beka, Thomas Ibsa; Bergh, Steffen G; Smirnov, Maxim; Birkelund, Yngve (Polar Research, 2017)
Source at: http://doi.org/10.1080/17518369.2017.1409586 Magnetotelluric (MT) data were recently collected on Brøggerhalvøya, Svalbard, in a 0.003–1000 s period range along a curved WNW–ESE profile. The collected data manifested strong three-dimensional (3D) effects. We modelled the full impedance tensor with tipper and bathymetry included in 3D, and benchmarked the result with determinant data two-dimensional (2D) inversion. The final inversion results indicated striking similarity with known surface bedrock geology and well reflected the tectonic history of the region. The most convincing contribution of the MT data is perhaps the elegantly imaged interplay between repeated basement-involved fold–thrust belt structures and successive down-dropped strata along steeply dipping oblique-normal faults (e.g., the Scheteligfjellet Fault) that created a horst/ridge and graben/depression system. Peculiarly, the MT result suggests that the Paleocene–Eocene fold–thrust belt structures dominate the shallow crustal level, while later normal faults in the area can be traced deeper into the pre-Devonian basement formations strongly affecting fluid and heat migration towards the surface. Near the sub-vertical Scheteligfjellet Fault, the MT model indicates aquifers within the upraised horsts of the pre-Devonian system at 2–5 km depth, sandwiched between the down-faulted resistive (ca. 500–3000 Ωm) Carboniferous and Permian successions. The section west of the Ny-Ålesund settlement has signatures of lateral and subvertical cap-rock sealings, surrounding a steep and deep-seated major fault and aquifer systems. This section of the peninsula therefore requires closer investigation to evaluate the deep geothermal resource prospect.